Quasiparticle scattering in type-II Weyl semimetal MoTe2. (15th February 2018) - Lin, Chun-Liang; Arafune, Ryuichi; Minamitani, Emi; Kawai, Maki; Takagi, Noriaki
Abstract: The electronic structure of type-II Weyl semimetal molybdenum ditelluride (MoTe2 ) is studied by using scanning tunneling microscopy and density functional theory calculations. Through measuring energy-dependent quasiparticle interference (QPI) patterns with a cryogenic scanning tunneling microscope, several characteristic features are found in the QPI patterns. Two of them arise from the Weyl semimetal nature; one is the topological Fermi arc surface state and the other can be assigned to be a Weyl point. The remaining structures are derived from the scatterings relevant to the bulk electronic states. The findings lead to further understanding of the topological electronic structure of type-II Weyl semimetal MoTe2 .